microWELT: Microsimulation projection of indicators of the economic effects of population ageing based on disaggregated national transfer accounts - Martin Spielauer; Gerard Thomas Horvath; Marian Fink; Gemma Abío; Guadalupe Souto; Concepció Patxot; Tanja Istenic (Austrian Institute of Economic Research (WIFO), 2020)
This paper studies how changes in the population composition by education and family characteristics impact on indicators of the economic effects of population ageing based on National Transfer Accounts (NTAs). NTAs constitute cross-sectional per-capita age-profiles of the key variables of national accounts consumption, income, saving, and public transfers, incorporating an estimation of private transfers. A variety of indicators based on NTA data combined with population projections was developed in the literature, of which we have selected two for our analysis: the Support Ratio (SR) and the Impact Index (IMP). We complement existing projections by using new disaggregated NTA data by education and family type, contrasting the results to the same indicators based on NTAs by age. Our projection analysis is performed using the dynamic microsimulation model microWELT. The model provides the required detailed socio-demographic projections and incorporates the NTA accounting framework. Our results show that indicators based on disaggregated data can give a very distinct picture of the economic effects of population ageing, as the burden of ageing is alleviated by the education expansion. Our study compares results for Austria and Spain.
Keywords: E01; J11; P51; O57; C53; 330; Microsimulation; Education; Demographic Change; National Transfer Accounts